Great opportunities ahead! Don't miss the boat! Where tech meets health care... - Reig, Juan; Valverde, Jose A.; Reig, Monica (EWMA Journal, 2015)
Technology is transforming almost everything in our daily lives, and there are few spaces or sectors not affected by this unavoidable change. However, sometimes our pace of coping with change is not always as good as it should be. In this article, we review recent technological breakthroughs and discuss ways by which they can improve the work of healthcare professionals and allow us to deliver better care to our patients. Which technologies will have the greatest impact on wound management and the closely related field of chronic care? We suggest that big data, 3D printing, communication and collaborative technologies, and innovative devices can lead to higher quality and more efficient care. Not only new technologies, but also new professional roles, societal challenges, and the sense of personal empowerment are deeply changing the way we deliver care. These factors in combination with advancements in medicine, genetics, neuroscience, new materials, nanosensors, increased consciousness about environment and energy as well as the influence of other non-medical disciplines opens the way for progress in the healthcare arena. Such advancements are closely tied to ethical, privacy, and security concerns that should be thoroughly considered.